Designing and implementing an exit communication test to gauge oral proficiency in a university - Chan, Swee Heng; Abdullah, Ain Nadzimah; Tan, Bee Hoon; Md Rashid, Sabariah; Chan, Mei Yuit; Tan, Helen (Inderscience Publishers, 2014)
Innovation in education is an encouraged enterprise that could help to solve problems relevant to education. In Malaysia, the lack of English language ability has been constantly identified as a factor that contributes to graduate unemployment. To address this concern, measures are exponentially explored to articulate some solid answers as a basis for educational change. In Universiti Putra Malaysia, an innovative and proactive step was taken to introduce an exit oral communication test (Universiti Putra Malaysia Test of Communication Skills in English). The in-house test enables a system-wide assessment and reporting of students' English oral language ability as the students exit university to the work world. This paper examines issues in the designing and implementation of an exit test with due attention given to its credibility and usability. The step-by-step procedural moves are described and some salient educational outcomes pertaining to the improving of English language competence are discussed.